1994
DOI: 10.1177/104063879400600326
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Serum Neutralization Test for the Detection of Antibody to Porcine Reproductive and Respiratory Syndrome Virus in Swine Sera

Abstract: Various conditions were evaluated and modified to improve the sensitivity of the serum neutralization (SN) test for detecting antibody in pigs infected with porcine reproductive and respiratory syndrome virus (PRRSV). Higher SN titers were consistently obtained by the addition of 20% fresh swine serum to the virus diluent and by the use of a permissive cell clone (MARC-145) derived from the MA-104 cell line. Test sera used to assess the SN test were obtained from 2 groups of 3-week-old pigs infected intranasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 9 publications
3
123
1
2
Order By: Relevance
“…These results are similar to a study, performed by Zuckermann et al [35], showing that vaccination with this commercial vaccine only resulted in an anamnestic humoral immune response after challenge. Virus-specific antibody titers as measured by IPMA or ELISA do not correlate with VN antibody titers and hence do not provide any information about protective immunity against PRRSV [33]. In the present experiment, the VN antibody response after infection in mock-vaccinated animals was delayed and weak, compared to the virus-specific antibody response.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results are similar to a study, performed by Zuckermann et al [35], showing that vaccination with this commercial vaccine only resulted in an anamnestic humoral immune response after challenge. Virus-specific antibody titers as measured by IPMA or ELISA do not correlate with VN antibody titers and hence do not provide any information about protective immunity against PRRSV [33]. In the present experiment, the VN antibody response after infection in mock-vaccinated animals was delayed and weak, compared to the virus-specific antibody response.…”
Section: Discussioncontrasting
confidence: 74%
“…This is in contrast with the study from Zuckermann et al [35] that showed an anamnestic VN antibody response in pigs that were vaccinated with this vaccine, and a study from Scortti et al [24] where vaccination with another inactivated PRRSV vaccine slightly improved the VN antibody response after challenge. This discrepancy may be due to the use of other tests with different sensitivity for the detection of VN antibodies [12,32,33,35]. Delrue et al [6] previously showed that inactivation of PRRSV with UV radiation or BEI does not influence the capacity of the inactivated virus to get internalized in PAM, the in vivo host cell type for the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The VN tests were performed in triplicates with 100 TCID50 of the virus/well as previously described [22]. To monitor humoral immune response following challenging of vaccinated pigs, an IIF using PRRSV infected MARC-145 cells as well as a competitive ELISA for detection of antibodies to PRRSV using recombinant E. coli-expressed N protein as antigen and a commercial indirect ELISA (IDEXX) for detection of anti-PRRSV antibodies were used as previously described [23].…”
Section: Virus Neutralization and Serological Testsmentioning
confidence: 99%
“…On this basis, the International Committee on Taxonomy of Viruses recently established a new order, Nidovirales, to contain the 2 families. 6,11 In infected cells, the approximately 15-kb From the USDA/ARS, Meat Animal Research Center, Clay Center, NE 68933 (Kwang, Yang) 15,22,25,26 All of these tests employ native viral antigens, which are produced in a tissue culture system. Among these tests, the ELISA is used routinely for PRRSV antibody detection.…”
mentioning
confidence: 99%